Peranan sokongan sosial terhadap kemurungan dalam kalangan remaja penagih dadah - Faizah Mat Isa; Rozmi Ismail; Norizan Hassan (Penerbit Universiti Kebangsaan Malaysia, 2018)
The number of adolescents involved in drug addiction increases every year. Statistic shows that in 2015 there were 6,406 addicts from age 13 to 24 years old compared to 4,954 detected in 2014. The majority of those addicts had major depression. It is predicted that by 2020, depression will be the second leading causes of global burden of diseases after heart disease. This study aims to identify the relationship between social support and depression among adolescent drug addicts. The study used quantitative method by distributing the questionnaires to respondents. A total of 367 adolescent drug adddicts were involved in this study. The results showed a significant negative relationship between social support and depression. The results of the study also showed that there were relationships between social support from guardian, friends and closed friends and depression. The implication of the study suggested that the role of social support such as family members and close friends are crucial to help adolecents cope with depression and addiction.